Neuropsychological and Psychiatric Outcomes in Dextro-Transposition of the Great Arteries across the Lifespan: A State-of-the-Art Review - Kasmi, Leila; Bonnet, Damien; Montreuil, Michèle; Kalfa, David; Geronikola, Nikoletta; Bellinger, David C.; Calderon, Johanna (Frontiers in Pediatrics, 2017)
Advances in prenatal diagnosis, perioperative management and postoperative care have dramatically increased the population of survivors of neonatal and infant heart surgery. The high survival rate of these patients into adulthood has exposed the alarming prevalence of long-term neuropsychological and psychiatric morbidities. D-Transposition of the Great Arteries (d-TGA) is one of the most extensively studied cyanotic congenital heart defect (CHD) with regards to neurodevelopmental outcomes. Landmark studies have described a common neurodevelopmental and behavioral phenotype associated with d-TGA. Children with d-TGA display impairments in key neurocognitive areas including visual-spatial and fine motor abilities, executive functioning, processing speed, and social cognition. As they grow older, they may face additional challenges with a worsening of deficits in higher-order cognitive skills, problems in psychosocial adjustment and a higher-than-expected rate of psychiatric disorders such as Attention Deficit Hyperactivity Disorder, depression and anxiety. The aim of this review is to summarize the available recent data on neuropsychological and psychiatric outcomes in individuals with d-TGA after the arterial switch operation. We present findings within a life-span perspective, with a particular emphasis on the emerging literature on adolescent and young adult outcomes. Finally, we propose avenues for future research in the CHD adult neuropsychology field. Among these avenues, we explore the potential mechanisms by which pediatric neurodevelopmental impairments may have life-long adverse effects as well as alternative interventions that could optimize outcomes.